2011
DOI: 10.5195/jyd.2011.186
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Reasons and Relationships Between Why Youth Join, Stay in, and Leave 4-H

Abstract: While the Minnesota 4-H Club program has grown over 29% in the last six years, annually over 25% of youth do not re-enroll. The Minnesota 4-H Retention Study asked youth who left the program why they decided to join, stay and ultimately leave 4-H. Data from 220 youth were examined to better understand the reasons for and relationship between youth joining and staying in 4-H and their reasons for leaving 4-H. Youth joined 4-H because they wanted to have fun, try new things, and participate in projects and fairs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Another limitation is that youth included in the study may potentially be only those who had positive experiences or felt motivated to participate. Although difficult, researchers can attempt to interview those who do not persist in leadership programs to further understand their experiences and what components are not conducive to positive outcomes (e.g., see Albright & Ferrari, 2010;Harrington et al, 2011). In the future, researchers can conduct mixed methods studies with youth from various demographic backgrounds, youth in other PYD programs, and program leaders; review curriculum documents; and conduct observations to triangulate the data regarding intentionality of program design, underlying mechanisms, and program outcomes.…”
Section: Limitationsmentioning
confidence: 99%
“…Another limitation is that youth included in the study may potentially be only those who had positive experiences or felt motivated to participate. Although difficult, researchers can attempt to interview those who do not persist in leadership programs to further understand their experiences and what components are not conducive to positive outcomes (e.g., see Albright & Ferrari, 2010;Harrington et al, 2011). In the future, researchers can conduct mixed methods studies with youth from various demographic backgrounds, youth in other PYD programs, and program leaders; review curriculum documents; and conduct observations to triangulate the data regarding intentionality of program design, underlying mechanisms, and program outcomes.…”
Section: Limitationsmentioning
confidence: 99%
“…Though the idea of legacy is ingrained in the organization, 4-H youth development professionals must start to recognize that youth and families without previous experience will require different support during recruitment and retention. Some work related to the retention of 4-H youth members within the 4-H program has been done, where the researchers concluded that youth who do not reenroll in 4-H do so because they lose interest, are not having enough fun or positive relationships, or because they become involved in other activities (Harrington et al, 2011). However, without understanding retention from a no-previous-4-H-experience lens, it will remain unclear what specifically deters the new populations we are recruiting from reenrolling in a 4-H program.…”
Section: Introductionmentioning
confidence: 99%
“…Youth join 4-H for a variety of reasons: a desire to have fun, to meet new friends, participate in projects, engage in community service, etc. (Harrington et al 2011;Wingenbach et al 2000).…”
mentioning
confidence: 99%
“…Attention to retaining members is important in minimizing dropouts. Reasons cited for dropout include: families not understanding the 4-H program, feeling unwelcome and that they do not belong, reduced time availability, not having the financial ability to pay for activities, and not having a positive learning experience in their projects (Defore et al 2011;Harrington et al 2011).…”
mentioning
confidence: 99%